The influence of curricula content on English sociology students' transformations: the case of feminist knowledge. Issue 4 (18th May 2016) - Abbas, Andrea; Ashwin, Paul; McLean, Monica
ABSTRACT: Previous research identifies the importance of feminist knowledge for improving gender equity, economic prosperity and social justice for all. However, there are difficulties in embedding feminist knowledge in higher education curricula. Across England, undergraduate sociology is a key site for acquiring feminist knowledge. In a study of four English sociology departments, Basil Bernstein's theoretical concepts and Madeleine Arnot's notion of gender codes frame an analysis indicating that sociology curricula in which feminist knowledge is strongly classified in separate modules is associated with more women being personally transformed. Men's engagement with feminist knowledge is low and it does not become more transformative when knowledge is strongly classified. Curriculum, pedagogy and gender codes are all possible contributors to these different relationships with feminist knowledge across the sample of 98 students.